2020
DOI: 10.31616/asj.2019.0067
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Pre- and Postoperative Health-Related Quality of Life Measures in Patients Who Have Had Decompression Surgery for Lumbar Spinal Stenosis

Abstract: Study Design: Retrospective chart audit.Purpose: This study aimed to investigate the gender difference in pre- and postoperative health-related quality of life (HRQOL) in patients who have had decompression surgery for lumbar spinal stenosis (LSS).Overview of Literature: Gender differences may contribute to variations in disease presentations and health outcomes. The influence of gender on pre- and postoperative HRQOL in spinal disorders remains unclear.Methods: We reviewed 125 patients (79 men and 46 women) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…These differences are not restricted to tactile perception and can be supposed for the whole body [82][83][84]. Regarding sex differences in clinical pain there are studies analysing pre-operative pain; a sex difference was found with greater pain scores for females than males [85][86][87][88][89], which was still detectable on the first post-operative day [86]. In terms of post-operative pain published data are inconsistent and depend partly on the time of the postoperative pain interviews [86,87,89].…”
Section: Use Of Over-the-counter Analgesicsmentioning
confidence: 99%
“…These differences are not restricted to tactile perception and can be supposed for the whole body [82][83][84]. Regarding sex differences in clinical pain there are studies analysing pre-operative pain; a sex difference was found with greater pain scores for females than males [85][86][87][88][89], which was still detectable on the first post-operative day [86]. In terms of post-operative pain published data are inconsistent and depend partly on the time of the postoperative pain interviews [86,87,89].…”
Section: Use Of Over-the-counter Analgesicsmentioning
confidence: 99%
“…Few studies have established this relationship through direct comparison of mental health outcome measures and there is an even greater scarcity in the literature when considering the cervical spine population. Individuals who underwent procedures for lumbar spine pathologies were reported to differ based on gender with respect to pain, disability, and mental health scores, as measured by SF-8 MCS [ 8 ]. Although Kobayashi et al [ 8 ] established a significant preoperative difference between genders, it was not maintained throughout the entire postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals who underwent procedures for lumbar spine pathologies were reported to differ based on gender with respect to pain, disability, and mental health scores, as measured by SF-8 MCS [ 8 ]. Although Kobayashi et al [ 8 ] established a significant preoperative difference between genders, it was not maintained throughout the entire postoperative period. A similar result was demonstrated in our study with the exception that genders did not differ in their preoperative PHQ-9, SF-12 MCS, or VR-12 MCS score.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations